2019
DOI: 10.1098/rsob.190074
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Long non-coding RNA LINC00467 regulates hepatocellular carcinoma progression by modulating miR-9-5p/PPARA expression

Abstract: The aim of this study was to analyse the expression pattern and elucidate the mechanistic involvement of long non-coding RNA LINC00467 in hepatocellular carcinoma (HCC). The relative expression of LINC00467 and microRNA (miR)-9-5p was determined by real-time polymerase chain reaction. Cell viability was measured using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay. The cell proliferation was analysed by cell counting. Cell migration and invasion were monitored by Transwell assay. The lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 25 publications
1
35
0
Order By: Relevance
“…LINC00467 , another lncRNA that was found to be downregulated in HCC, has been studied as a potential therapeutic target thanks to its role as an antagomir for miR-9-5a , which targets peroxisome proliferator-activated receptor alpha ( PPARA ) for silencing [ 140 ]. LINC00467 ectopically expressed in HCC cells conduced to antiproliferative effects and, like miR503HG , checked migration and invasion.…”
Section: Noncoding Rnasmentioning
confidence: 99%
“…LINC00467 , another lncRNA that was found to be downregulated in HCC, has been studied as a potential therapeutic target thanks to its role as an antagomir for miR-9-5a , which targets peroxisome proliferator-activated receptor alpha ( PPARA ) for silencing [ 140 ]. LINC00467 ectopically expressed in HCC cells conduced to antiproliferative effects and, like miR503HG , checked migration and invasion.…”
Section: Noncoding Rnasmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) is one of the most widespread cancers, and it has an extremely poor prognosis, contributing to nearly 662,000 deaths per annum [1,2]. The incidence rate of HCC is ranked sixth-highest of the cancerous tumors globally, and the number of deaths caused by HCC is ranked third-highest of the tumor-related deaths [3].…”
Section: Introductionmentioning
confidence: 99%
“…LINC00467 is a novel lncRNA localized at the chromosomal locus 1q32. 3, and has been reported to be markedly dysregulated in hepatocellular carcinoma [14], lung adenocarcinoma [15] and neuroblastoma [16]. Additionally, it has been confirmed that LIN C00467 could promote cell proliferation, migration and invasion of lung adenocarcinoma cells [17].…”
Section: Ivyspring International Publishermentioning
confidence: 82%